2017
DOI: 10.1016/j.msea.2017.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of strain-induced TRIP and propagative PLC bands in Medium Mn steels

Abstract: An Fe-0.2C-5Mn-2.5Al medium manganese steel is studied for three different intercritical annealing temperatures T IA to observe the effects of variations of retained austenite stability on the mechanical work hardening in uniaxial tension. Digital image correlation (DIC) showed that both Lüders bands and type A Portevin-le-Châtelier (PLC) bands occurred in samples with a lower T IA , but both disappeared when T IA was increased. In-situ measurements of sample magnetization with a correction for stress effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 47 publications
6
40
0
2
Order By: Relevance
“…At the same time, the intercritical annealing resulted in a softening of the material with improved ductility. In previous studies, it was pointed out the intercritical annealing temperature has a great effect on the fraction and stability of retained austenite [10,[48][49][50][51][52]. Consequently, the mechanical properties showed a strong dependence on intercritical annealing temperature ( Figure 10).…”
Section: Influence Of Intercritical Annealing Temperature On the Thermentioning
confidence: 88%
“…At the same time, the intercritical annealing resulted in a softening of the material with improved ductility. In previous studies, it was pointed out the intercritical annealing temperature has a great effect on the fraction and stability of retained austenite [10,[48][49][50][51][52]. Consequently, the mechanical properties showed a strong dependence on intercritical annealing temperature ( Figure 10).…”
Section: Influence Of Intercritical Annealing Temperature On the Thermentioning
confidence: 88%
“…The range of deformation when serration occurred is variable. In contrast, for the specimens deformed at 100 °C and 140 °C, the oscillations were observed in the final stage of deformation (Figure 2c Some typical features for the PLC effect [14][15][16][17][18][19][20]28] were observed for the investigated steel deformed at elevated temperatures: 60-140 • C. The characteristic serrations were observed on the stress-strain curves ( Figure 2). The specimen deformed at 20 • C showed no evidence of the PLC effect (Figure 2a).…”
Section: Mechanical Behaviormentioning
confidence: 90%
“…Gibbs et al [26] proposed the theory that the characteristic serration is related to the various martensitic transformation rates during plastic deformation. Callahan et al [14] observed that the TRIP effect and the passage of both Lüders and PLC bands occur simultaneously in 0.2C-5Mn-2.5Al medium-Mn steel. Sun et al [15] reported that plastic instability in 0.26C-11.6Mn-2.7Al steel was related to discontinuous strain-induced martensite transformation.…”
mentioning
confidence: 99%
“…According to Medvedeva et al in the presence of Mn a Mn-C pair forms that reduces the expected increase in the fault energy that is caused by C alone. [25] Dynamic strain aging is a common observation in medium-Mn steels [4,5,7,10,12,[26][27][28][29][30] with a wide variation in processing. Gibbs et al [10] investigated a 7Mn steel annealed at temperatures varying from 848 K to 948 K (575°C to 675°C) for 168 hours.…”
Section: B Dynamic Strain Agingmentioning
confidence: 99%
“…Zhang et al reports that the starting structure of the investigated steels was primarily a-ferrite (67 vol pct) with the remainder of the microstructure being c-austenite. Recent works [27][28][29][30] with medium-Mn steels on the PLC effect have shown that there is a strain-induced transformation of c-austenite to a-martensite within the PLC band. This effect is attributed to the high localized plastic deformation leading to the strain induced transformation of cfia-martensite.…”
Section: B Dynamic Strain Agingmentioning
confidence: 99%